Autophagy and IL-1 Family Cytokines - Harris, James (Frontiers in Immunology, 2013)
Autophagy is an important intracellular homeostatic mechanism for the targeting of cytosolic constituents, including organelles, for lysosomal degradation. Autophagy plays roles in numerous physiological processes, including immune cell responses to endogenous and exogenous pathogenic stimuli. Moreover, autophagy has a potentially pivotal role to play in the regulation of inflammatory responses. In particular, autophagy regulates endogenous inflammasome activators, as well as inflammasome components and pro-IL-1β. As a result, autophagy acts a key modulator of IL-1β and IL-18, as well as IL-1α, release. This review focuses specifically on the role autophagy plays in regulating the production, processing and secretion of IL-1 and IL-18 and the consequences of this important function.